Al-Taaruf Sebagai Konstruksi Relasi Gender Perspektif Al-Quran - Ikhwanuddin, Mohammad (Islam Kontemporer, 2016)
In Islam, the discussion on gender relations have undergone significant developments. This development is not only related to the wealth of experience that has been passed over the last few years, but also the serious attention of Muslim scholars in a re-interpretation of the classic literature that provides a high spirit into the foundations of gender relations. One timeless classic literature of the times is the Qurâan. In the distribution of its verses, the Quran provide clues to understanding the pattern of gender relations. One such clue is the verses of the Qurâan to review explicitly about gender identity. Tracking and documenting the identity of the Qurâan diction is then narrowed to the Surat al-Hujurat verse 13. Interpretation of that paragraph provides a new paradigm that looked at gender relations is not only related to gender identity and their alignment patterns in beberaba field. However, the construction of the Qurâan regarding gender relations requires a construction formula with crochet toward informed consent Allah through the Qurâan. Construction of gender relations in the form of al-taarof. Interpretation of al-taaruf provides a narrative of the Qurâan that to link between gender identity, formula construction, as well as the direction of the goal.